factor of 6x^2-7x-3? please it’s urgent​

Question

factor of 6x^2-7x-3? please it’s urgent​

in progress 0
Delilah 2 weeks 2021-10-04T16:46:52+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-04T16:48:10+00:00

    Answer:

    (3x+1)(2x-3)

    Step-by-step explanation:

    6x^{2} – 7x + 3

    = 6x^{2} – (9-2)x + 3

    = 6x^{2} -9x + 2x – 3

    = 3x(2x-3) + 1(2x-3)

    = (3x+1)(2x-3)

    0
    2021-10-04T16:48:51+00:00

    Answer:

    Factor: y=6×2+7x−3

    Ans: (3x + 1)(2x – 3)

    Explanation:

    Use the new AC Method. y = 6(x – p)(x – q)

    Converted trinomial: y’=x2+7x−18 = (x – p)(x – q)

    p’ and q’ have opposite signs (Rule of signs).

    Factor pairs of 18 –> (-1. 18)(-2, 9). This sum is 7 = -b.

    Then p’ = 2 and q’ = -9.

    Therefor, p=(p’a)=26=13 and q’=−96=−32

    y = 6(x + 1/3)(2x + 3) = (3x + 1)(2x – 3)

    Step-by-step explanation:

    Hope it help you

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )